Why Psychology hub? - Gazzillo, Francesco; Livi, Stefano (Psychology Hub, 2020)
Established in 2020, Psychology hub is a new scientific journal that inherits the tradition established by its predecessor Rassegna di Psicologia (last issue 2020, vol. 37, issue 1), directed over the last thirty-six years by relevant exponents of Italian academic psychology such as Nino Dazzi and Gian Vittorio Caprara, who founded it, and then by Clotilde Pontecorvo, Anna Silvia Bombi, Renata Tambelli and Fiorenzo Laghi. Why the name Psychology hub (PsyHub)? In 2002 John Petty, in his presidential column of the Association for Psychological Science, described psychology as a hub science (Cacioppo, 2007) underlining the new role that psychology has acquired among the various scientific disciplines. If observing the cross citations of different contemporary science disciplines in the articles, seven “hub sciences” can be indeed identified: mathematics, physics, chemistry, earth sciences, medicine, social sciences, and psychology. So, based on the map of reciprocal citations of scientific papers, psychology emerged as one of the central disciplines of science. As psychology operates on a breadth of domains and it dialogues with many other sciences, it becomes, as a matter of fact, interdisciplinary by nature. For example, the analysis of citations has indicated that public health, neuroscience, neurology, and genetics are among the sciences that fall between psychology and medicine, as well as education or gerontology fall between psychology and social sciences. In the modern trend that encourages each specific area of psychology to become more and more specialized, PsyHub aims to connect different disciplines and theoretical paradigms of psychology becoming an exchange point and making readers attentive and curious about possible stimuli from other psychology areas. The papers published in PsyHub aims to be an explicit point of connection and a stimulus for our and other scientific disciplines. The main goal is to keep psychologists up-to-date on the latest research findings and to provide a forum for psychology, psychiatry and mental health professionals to share their findings with researchers and clinicians. The forum will accept English written papers only to ensure the exchange to an international audience. To sum up, PsyHub is an international peer-reviewed Open Access journal publishing original research in different areas of psychology, including: Behavioral Psychology, Clinical Psychology, Cognitive Psychology, Developmental Psychology, Educational Psychology, Environmental Psychology, Family Psychology, Health Psychology, Measurement/Assessment, Psychodynamics, Psychotherapy, School Psychology, Social Psychology, Sport Psychology, Work, Industrial and Organizational Psychology. PsyHub focuses on original empirical contributions, but is also open to theoretical articles, critical reviews and replications of published research.